Learning management of the Amtsilati method for accelerating Kitab Kuning mastery: Evidence from an Indonesian majelis taklim - Retno Tutut Nur Wana (Eduvista: Journal of Education and Innovation, 2026)
The mastery of Kitab Kuning through the Amtsilati method has been widely investigated; however, the relationship between the implementation of learning management, contextual factors, and the accelerated mastery of Kitab Kuning remains insufficiently understood. This study aims to analyze the implementation of learning management in the Amtsilati method and its implications for accelerating Kitab Kuning mastery. A qualitative case study was conducted in Majelis Taklim Amtsilati Nurul Jadid, Patebon Village, Kejayan District, Pasuruan Regency, Indonesia. Data were collected through observations, semi-structured interviews, and document analysis and were analyzed using the interactive model developed by Miles, Huberman, and Saldaña. The findings reveal that the implementation of the functions of planning, organizing, actuating, and controlling, supported by teacher competence, systematic Amtsilati modules, a conducive learning environment, student motivation, and effective management of learning barriers, contributes to more effective learning, improved understanding of Nahwu-Sharaf, and enhanced Kitab Kuning reading proficiency. This study proposes a conceptual model explaining the relationships among learning management, contextual factors, and the accelerated mastery of Kitab Kuning, thereby contributing to the advancement of learning management theory and practice in majelis taklim. Abstrak Penguasaan Kitab Kuning melalui metode Amtsilati telah banyak dikaji, namun hubungan antara implementasi manajemen pembelajaran, faktor-faktor kontekstual, dan percepatan penguasaan Kitab Kuning masih belum dijelaskan secara komprehensif. Penelitian ini bertujuan untuk menganalisis implementasi manajemen pembelajaran metode Amtsilati serta implikasinya terhadap percepatan penguasaan Kitab Kuning. Penelitian ini menggunakan pendekatan kualitatif dengan desain studi kasus yang dilaksanakan di Majelis Taklim Amtsilati Nurul Jadid, Desa Patebon, Kecamatan Kejayan, Kabupaten Pasuruan, Indonesia. Data dikumpulkan melalui observasi, wawancara, dokumentasi, dan dianalisis menggunakan model analisis interaktif Miles, Huberman, dan Saldaña. Hasil penelitian menunjukkan bahwa implementasi fungsi planning, organizing, actuating, dan controlling, yang didukung oleh kompetensi guru, modul Amtsilati, lingkungan belajar yang kondusif, motivasi santri, serta pengelolaan hambatan pembelajaran, berkontribusi terhadap pembelajaran yang lebih efektif, peningkatan pemahaman nahwu-sharaf, dan kemampuan membaca Kitab Kuning. Penelitian ini menawarkan sebuah model konseptual yang menjelaskan hubungan antara manajemen pembelajaran, faktor-faktor kontekstual, dan percepatan penguasaan Kitab Kuning, sehingga memberikan kontribusi bagi pengembangan manajemen pembelajaran di lingkungan majelis taklim.